Behavioral Political Economy Analysis of Legal and Illegal K-Beauty and K-Health Products on Indonesian Women: Study Case of Post-COVID-19 Pandemic - Mulyaman, Darynaufal; Ismail, Achmad (Universitas Gadjah Mada, 2023)
As the K-Pop phenomenon in the world increases, there is increasing concern about physical appearance, especially oriental appearance. The phenomenon can be seen in the phenomenon of people who buy Korean cosmetics or even plastic surgery to have similarities with Korean pop stars. No exception in Indonesia, the phenomenon is also present in the community, especially among women. However, data on the behavior of Indonesian women to have similar oriental features such as Korean pop stars, especially post-pandemic, are not yet comprehensively available. Therefore, this study aims to find out how is the behavior of Indonesians, especially women, who purchase K-beauty and K-health products, legal and illegal, to improve their appearance to embrace the K-Pop beauty standard and its implications for Indonesia's political economy. This study considers that this research needs to be done to explore the behavioral political economy analysis of females from Indonesia who are looking for K-Beauty and K-Health products, legal and illegal, to improve their appearance, for a more collaborative understanding of the policy-making and education process of the public in the field of public health policy related to aesthetic beauty care or medical education for women, nationally and regionally, especially after the COVID-19 pandemic.